2014
DOI: 10.1038/srep06126
|View full text |Cite
|
Sign up to set email alerts
|

Charge-Transfer Induced Magnetic Field Effects of Nano-Carbon Heterojunctions

Abstract: Room temperature magnetic field effects have not been definitively observed in either single-walled carbon nanotubes (SWCNTs) or C60 under a small magnetic field due to their weak hyperfine interaction and slight difference of g-factor between positive and negative polarons. Here, we demonstrate charge-transfer induced magnetic field effects in nano-carbon C60-SWCNT bulk heterojunctions at room temperature, where the mechanism of magnetic field effects is verified using excited state transition modeling. By co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…Their work revealed that population mixing due to resonant excitation causes a net change in the exciton-polaron reaction rate [29]. Also, Qin et al investigated the magnetic field effect through calculation of magnetic field dependent singlet and triplet ratios [30][31][32]. These indicated the importance of excitons in organic magnetic field effect from either experimental or theoretical aspects.…”
Section: Introductionmentioning
confidence: 99%
“…Their work revealed that population mixing due to resonant excitation causes a net change in the exciton-polaron reaction rate [29]. Also, Qin et al investigated the magnetic field effect through calculation of magnetic field dependent singlet and triplet ratios [30][31][32]. These indicated the importance of excitons in organic magnetic field effect from either experimental or theoretical aspects.…”
Section: Introductionmentioning
confidence: 99%
“…An intriguing question is whether intermolecular radicals and excitation processes play an important role for magnetic‐energy harvesting in BCCT materials . Magnetic‐field effects are critical to reveal and elucidate charge‐transfer controlled intermolecular radicals and excited processes in BCCTs, where the external magnetic field can induce the spin mixing of singlet and triplet CT, and leads to the change of polarons and triplet excitons . The BCCTs exhibit magnetic‐field‐dependent capacitance in which the magnetic field and capacitance oscillate in phase ( Figure a) .…”
mentioning
confidence: 99%
“…With increasing incident light intensity (355 nm), more electron–hole pairs are generated in perovskite layer. External magnetic field could increase the ratio of triplet electron–hole pair . Because dissociation rate of singlet state is smaller than that of triplet, carrier density becomes larger under external magnetic field.…”
Section: Resultsmentioning
confidence: 99%